Crowding-Out Effect: Evidence from OECD Countries - Mehmet Emre Ünsal (İstanbul İktisat Dergisi)
The concept of the crowding-out effect, which is used to describe how an expansionary fiscal policy would reduce private investments, has become one of the major areas of research in the economy. This study aims to investigate whether or not the crowding-out effect is applicable in OECD countries. For this purpose, Panel Data Analysis was performed for the period 1995-2017. This analysis uses private investments of countries as dependent variables and, in addition to GDP and total government expenditures, it uses education, health, general public services, social protection, economic affairs, defence, public order and safety expenditures of the government as independent variables. Panel Data Analysis was performed using Huber-Eicker-White Estimator in line with the results of econometric tests required for this analysis such as stationarity, model determination, heteroscedasticity and autocorrelation. As a result, in OECD countries, while economic growth and defence expenditures of the government positively affect private investments, total government expenditures and social protection expenditures of the government have a crowding-out effect on private investments.